Federal State Unitary Enterprise "All-Russian Research and Design-Technological Institute of the rolling stock of the Ministry of Railways of the Russian Federation") - Kossov, V. S. (Science and Transport Progress, 2004)
Some results of designing a three-piece bogie of a freight car with the help of a precise computer model are presented. The computer model is developed using the Universal Mechanism software. The Hierarchy Analysis Process is applied to choose the rational solution in the parameter space of the model.